Association Between Serum IGF-1 and Diabetes Among U.S. Adults - Teppala, Srinivas; Shankar, Anoop (Diabetes care, 2010)
OBJECTIVE: Serum insulin-like growth factor (IGF)-1 may have a role in the maintenance of glucose homeostasis. We examined the association between serum IGF-1 and diabetes in a representative sample of U.S. adults. RESEARCH DESIGN AND METHODS: Third National Health and Nutrition Examination Survey (NHANES III) participants aged ≥18 years (n = 5,511) were the subjects of the study. The main outcome was the presence of diabetes (n = 387). RESULTS: Lower serum IGF-1 levels were positively associated with diabetes after adjusting for age, sex, race/ethnicity, education, smoking, alcohol intake, BMI, hypertension, glomerular filtration rate, and serum cholesterol. Compared with quartile 4 of IGF-1 (referent), the odds ratio (OR) of diabetes associated with quartile 1 was OR 2.16 (95% CI 1.24-3.76); P-trend = 0.002. However, the observed association between IGF-1 and diabetes was present only in those <65 years of age (OR = 3.05; P-trend = 0.006) and disappeared in those ≥65 years of age (OR = 0.51; P-trend = 0.18); P-interaction = 0.0056. CONCLUSIONS: Low IGF-1 levels are associated with diabetes among young subjects.